GAMBARAN TINGKAT PENGETAHUAN DAN SIKAP ORANG TUA/PENGASUH SISWA/SISWI SMA MENGENAI PERKAWINAN ANAK UNTUK MENEKAN ANGKA STUNTING DI WILAYAH KEK MANDALIKA - Ni Wayan Devian Aishwarya (Jurnal Medika Hutama, 2024)
Stunting is a chronic nutritional disorder caused by inadequate nutritional intake, repeated infections, and lack of psychosocial stimulation that impacts growth and development. Stunting is caused by many factors including low parental education, poverty, poor water and sanitation, slum geographic conditions, and child marriage. Child marriage is a marriage carried out by one or both brides and grooms who are not in accordance with the age of marriage, which is a minimum of 19 years. Informal education is provided by parents as the primary and most important educatorshave the knowledge and attitudes that need to be applied to their children. The purpose of this study was to determine the level of knowledge and attitudes of parents/caregivers of high school students regarding child marriage to reduce stunting rates in the Mandalika Special Economic Zone. This study is a descriptive study with a cross-sectional approach. The respondents of the study were parents/caregivers of high school students totaling 97 respondents in the Mandalika Special Economic Zone. The sampling method used was simple random sampling. Data collection through questionnaires. Data analysis using univariate tests. The results of the study show that level of knowledge of parents/caregivers of students regarding child marriage is high and the attitudes of parents/caregivers of students do not support child marriage in the Mandalika Special Economic Zone, Central Lombok Regency.